IMPROVEMENT OF STUDENT'S CRITICAL THINKING ABILITY THROUGH PROBLEM-SOLVING ON THE EVALUATION OF EDUCATION POLICY - Aman Aman (ISTORIA: Jurnal Pendidikan dan Sejarah, 2019)
ABSTRAKPenyelenggaraan program magister adalah untuk membekali mahasiswa memiliki berbagai kecakapan baik akademik, spiritual, sosial, maupun keterampilan. Berkaitan dengan kecakapan akademik, maka salah satunya mahasiswa dituntut untuk memiliki kemampuan berpikir kritis, yang pada akhirnya mahasiswa diharapkan memiliki kecakapan dalam menyelesaikan permasalahan disertai dengan kemampuan merumuskan alternative-alternatif solusi permasalahan yang ada di dalam diri dan masyarakatnya. Penelitian ini bertujuan untuk: 1) mengetahui bagaimana meningkatkan kemampuan berpikir kritis mahasiswa melalui implementasi metode problem solving pada mata kuliah evaluasi kebijakan pendidikan, 2) bagaimana peningkatan kemampuan berpikir kritis mahasiswa dengan implementasi metode problem solving dalam pembelajaran mata kuliah evaluasi kebijakan pendidikan. Penelitian ini menggunakan metode Classroom Action Research. Hasil penelitian menunjukkan bahwa: Penerapan metode perkuliahan problem solving dapat meningkatkan kemampuan berpikir kritis mahasiswa dalam proses perkuliahan system informasi manajemen mutu pendidikan. Hal tersebut dapat dibuktikan dengan adanya peningkatan kemampuan berpikir kritis mahasiswa pada setiap siklus. Kata Kunci: berpikir kritis, problem solving, dan evaluasi kebijakan. ABSTRACTThe holding of a master's program is to equip students to have a variety of skills, both academic, spiritual, social, and abilities. Related to academic skills, one of them is students who are required to have critical thinking skills, which in the end, students are expected to have the ability to solve problems accompanied by the ability to formulate alternative solutions to the issues that exist in themselves and their communities. This study aims to: 1) find out how to improve students 'critical thinking skills through the implementation of problem-solving methods in educational policy evaluation courses, 2) how to improve students' critical thinking skills by implementing problem-solving methods in learning education policy evaluation courses. This research uses the Classroom Action Research method, which is carried out through the steps of planning, implementation and observation, and reflection. Data sources are students who take education policy evaluation courses. The results showed that: The application of the problem-solving lecture method can improve students' critical thinking skills in the education quality management information system lecture. Keywords: critical thinking, problem-solving, and policy evaluation.